2020
DOI: 10.1089/tmj.2018.0264
|View full text |Cite
|
Sign up to set email alerts
|

The Harvey–Bradshaw Index Adapted to a Mobile Application Compared with In-Clinic Assessment: The MediCrohn Study

Abstract: Objectives: Mobile apps are useful tools in e-health and selfmanagement strategies in disease monitoring. We evaluated the Harvey-Bradshaw index (HBI) mobile app self-administered by the patient to see if its results agreed with HBI in-clinic assessed by a physician. Methods: Patients were enrolled in a 4-month prospective study with clinical assessments at months 1 and 4. Patients completed mobile app HBI and within 48 h, HBI was performed by a physician (gold standard). HBI scores characterized Crohn's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…However, clinicians tended to track the change in HBI/SCCAI, rather than the absolute score, to understand their severity. Echarri et al 12 compare patient-reported HBI on smartphones to clinician-reported HBI and confirmed a sensitivity of 92% and specificity of 94%. Clinician and participant feedback showed that participants tended to score themselves higher than clinicians on self-examination and extraintestinal manifestations.…”
Section: Discussionmentioning
confidence: 91%
“…However, clinicians tended to track the change in HBI/SCCAI, rather than the absolute score, to understand their severity. Echarri et al 12 compare patient-reported HBI on smartphones to clinician-reported HBI and confirmed a sensitivity of 92% and specificity of 94%. Clinician and participant feedback showed that participants tended to score themselves higher than clinicians on self-examination and extraintestinal manifestations.…”
Section: Discussionmentioning
confidence: 91%
“…Comprehensiveness was also rated insufficient in 18 other instruments; however, the reviewers’ rating was decisive in all of those cases, as no content validity studies or clear development studies on comprehensiveness were identified. Only the HBImApp 55 had a doubtful quality content validity study on comprehensiveness, though the criteria for comprehensiveness were rated as indeterminate. The EIBDQ 76 was the only instrument rated insufficient for all three aspects.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, for long-term gastrointestinal disorders, such as IBD, which are characterized by an unstable disease course with recurrent remission and exacerbation, mHealth apps could be a promising approach for symptom monitoring with an early detection of disease relapse. As previous studies have shown that self-reporting symptom diaries correlate with disease activity index for Crohn disease [ 70 , 71 ], validated symptom assessment questionnaires could be implemented in future mHealth apps.…”
Section: Discussionmentioning
confidence: 99%